SINTESIS NANOKITOSAN TERMODIFIKASI NATRIUM KLORIDA DAN APLIKASINYA SEBAGAI PENGAWET KAYU SENGON (Falcataria moluccana) - Annisa Primaningtyas; Tomy Listyanto; Ganis Lukmandaru (Journal Penelitian Kehutanan FALOAK, 2022)
Chitosan is an environmentally friendly natural preservative. In this study, nanometer-sized chitosan (nanochitosan) modified with NaCl was used as a sengon wood (Falcataria moluccana) preservative. The NaCl addition aimed to make the nanoparticle stable which was affected by chitosan concentration and the dispersion storage time. This study applied nanochitosan as a wood preservative by observing the concentration of chitosan and the storage time factor of nanochitosan dispersion. The samples were tested its anti-termite properties against dry wood termites (Cryptotermes cynocephalus Light), observed the morphology and size of nanochitosan in wood by Scanning Electron Microscopy (SEM) and particle size analyzer (PSA). ANOVA results showed no significant effect of concentration and storage time factors on preservation test parameters, but interesting things were found in this study. The particle size of the preservative affected the distribution on the surface. Samples preserved with nanochitosan with varying sizes had termite bites that were evenly distributed throughout the surface. On the other hand, samples preserved with uniformly sized nanochitosan had centered termite bites in several spots of surfaces. It was due to the particle sizes diversity influenced by storage time which provokes the agglomeration and determines the particles distribution in the preservative dispersion and wood surfaces.